ADDED VALUES OF SOCIAL CRM: THE EXAMINATION OF CUSTOMER PERSPECTIVE - Amila Pilav-Velic; Anes Hrnjić; Ljubica Milanović Glavan; Azra Hanić (Economic Review)
Background: Social media allow companies to create more “friendly” and personal interaction with their customers on an individual basis affecting the relationship development. Generally, people have more confidence in their friends’ recommendations. On the other hand, companies prefer this type of direct and targeted communication considering its reasonably lower costs, greater ability to target specific categories of visitors, the speed of response, etc. This paper aims to investigate the characteristics and benefits of using Social Cutomer Relationship Management (or abbreviated SCRM) for developing relations that many customers nowadays perceive as the most valuable component of the business offer. The most important characteristics of SCRM were examined using factor analysis and logistic regression in order to explore how respondents’ gender and variables with highest weight from each factor relate to customers’ choice of social media-based interaction. Sampling technique was applied via an online questionnaire containing four sections of questions with a link posted to ensure a greater response rate for analysis. This study indicates that the most significant added values of SCRM compared to traditional CRM, of often called classic CRM, are: customers’ mutual collaboration and interactions, customers’ engagement and interactions with company, available and flexible interaction, and customers’ involvement. The final logistic model indicates that two variables were statistically significant for the probability of making decision on further interaction. Paper provides some important practical contributions, offering managers a framework of important factors that need to be considered when planning and implementing their CRM strategies. Precisely, they can establish and adjust their social-media based interaction in line with identified added values from customer perspective.